1995
DOI: 10.1007/bf01076568
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of glycogen synthase activation in isolated hepatocytes

Abstract: Glycogen synthase, the regulatory enzyme of glycogen synthesis undergoes multisite phosphorylation leading to its inactivation. The kinases responsible for this covalent modification (ex. cAMP-dependent protein kinase, protein kinase C and glycogen synthase kinase-3) are controlled by the second messengers generated by different hormones. The isolated hepatocytes has been used as one of the experimental models for studying this complex regulatory process. Inactivation of glycogen synthase by glucagon and vasop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…of GSK-3 and subsequent activation of glycogen synthase a in isolated hepatocytes (Pugazhenthi & Khandelwal 1995). In the present study, by using Ro 31-8220, a staurosporine derivative and potent bisindolylmaleimide inhibitor of several PKC isoforms -mainly , 1 , 11 , and´ (Wilkinson et al 1993), a moderate, although significant, inhibition of the GLP-1-induced increase in glycogen-synthase a activity was detected, as previously observed in rat hepatocytes (Redondo et al 2003).…”
Section: Figuresupporting
confidence: 84%
“…of GSK-3 and subsequent activation of glycogen synthase a in isolated hepatocytes (Pugazhenthi & Khandelwal 1995). In the present study, by using Ro 31-8220, a staurosporine derivative and potent bisindolylmaleimide inhibitor of several PKC isoforms -mainly , 1 , 11 , and´ (Wilkinson et al 1993), a moderate, although significant, inhibition of the GLP-1-induced increase in glycogen-synthase a activity was detected, as previously observed in rat hepatocytes (Redondo et al 2003).…”
Section: Figuresupporting
confidence: 84%
“…The serine/threonine protein kinase GSK-3 inhibits GS by phosphorylation (3) and is considered to be a major regulator of GS in several cell types including liver cells (1). We investigated the effect of insulin and bpV(phen) on GSK-3 activity and found that both agents were comparably inhibitory (Fig.…”
Section: Insulin and Bpv(phen) Modulation Of Pkb/akt And Gsk-3 Activimentioning
confidence: 99%
“…Whereas there have been numerous studies of GS activation in skeletal muscle, the modulators of GS in liver have been less completely evaluated. Studies to date indicate that glucose and insulin are the major physiologic effectors of hepatic GS activation (1,2). It appears that glucose and/or its metabolite glucose 6-phosphate activate hepatic GS by physically associating with critical regulatory enzymes upstream of GS or with GS itself (2,4,5), although other mechanisms have been suggested (6).…”
mentioning
confidence: 99%
“…This regulation of GSK-3β is influenced by cell stressors such as hypoxia, oxidative stress, heat shock, but also by factors such as changes in glucose concentration and high GDP content. Although these physicochemical properties are important non-physiological characteristics of various PDF (Pugazhenthi and Khandelwal 1995;Cuzzocrea et al 2007), a direct association between GSK-3β and PD has not yet been described.…”
Section: Introductionmentioning
confidence: 99%